Evaluation of fetal cardiac morphology and function in hypertensive disorders of pregnancy using Fetal HQ technology combined with uterine artery ultrasound parameters - Wang, Lu; Fu, Xinghui; Ren, Xiaoyu; Guo, Yu; Zhou, Haixia; Yue, Hongli; Song, Chunjing; Zhang, Danhua; Li, Gang; Li, Wenrui; Zhang, Pengjie (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveHypertensive disorders of pregnancy (HDP) significantly affect both maternal and fetal health, with uterine artery hemodynamic parameters playing a critical role in assessing fetal well-being, though they do not provide early insights into fetal cardiac function. Fetal Heart Quantification (Fetal HQ) technology offers a non-invasive, highly accurate method for evaluating fetal heart morphology and function, making it a valuable tool for assessing the impact of HDPs on fetal cardiac health.MethodsThis study investigates fetal heart function and morphology in hypertensive disorders of pregnancy (HDPs) using fetal heart quantification (HQ) technology combined with uterine artery ultrasound parameters. A total of 70 normal fetuses and 59 fetuses with HDPs were included, with 30 cases showing normal and 29 cases showing abnormaluterine artery blood flow patterns. Uterine artery hemodynamic parameters (PI, RI, S/D) and fetal echocardiographic parameters (FRAC, FS, GLS, EF, 4CVCirc, GSI) were assessed.ResultsResults showed that in the HDP group with abnormal uterine artery blood flow, PI, RI, and S/D were significantly higher than in both the control and HDP groups with normal blood flow (P < 0.05). Right ventricular function, including FRAC, GLS, and FS, was significantly decreased in the HDP group with abnormal blood flow, while 4CVCirc and GSI were significantly different from controls. Left ventricular function showed no significant differences. The area under the ROC curve for predicting fetal heart morphology and function via multiple right ventricular parameters was 0.901, and 0.825 for right heart function.ConclusionThese findings suggest that the fetal right ventricle is more sensitive to hemodynamic changes in HDP pregnancies, with right heart functional and morphological indicators potentially serving as predictive markers.